2017
DOI: 10.12973/eurasia.2017.00939a
|View full text |Cite
|
Sign up to set email alerts
|

E-Assessment and Computer-Aided Prediction Methodology for Student Admission Test Score

Abstract: Machine Learning is a scientific discipline that addresses learning in context is not learning by heart but recognizing complex patterns and makes intelligent decisions based on data. Currently, students have to face the problem of selecting the best suitable university for admission in engineering. There is no predictor system that recommends the students to select the specific category which is best to its academic career. Students have to first appear in the entry test and can't predict whether he/she can p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…In the first stage of the literature review, we found that only a single technique was used to analyze student educational data in many approaches that are frequently used. For example, Usman et al (2017) tools were developed to predict student entry tests using regression technique. They used demographic data obtained from 5,042 students at the University of Engineering and Technology, Pakistan such as academic data, age, gender, and interests.…”
Section: Applying Machine Learning To Predict Student Performancementioning
confidence: 99%
See 1 more Smart Citation
“…In the first stage of the literature review, we found that only a single technique was used to analyze student educational data in many approaches that are frequently used. For example, Usman et al (2017) tools were developed to predict student entry tests using regression technique. They used demographic data obtained from 5,042 students at the University of Engineering and Technology, Pakistan such as academic data, age, gender, and interests.…”
Section: Applying Machine Learning To Predict Student Performancementioning
confidence: 99%
“…In an educational context, machine learning techniques are a potential approach widely used to accomplish the problems of predicting education outcomes, forecasting student behavior and improving educational quality. This is primarily applied to predict and support decision-making such as analyzing student behavior demography (Bilal et al, 2022;Kaensar & Wongnin, 2023), predicting student performance (Usman et al, 2017;Yagci, 2022), and identifying the relationship between student data and their achievement (Chang & Wang, 2016;Qahmash et al, 2023). However, although those published works could provide educational benefits, those features, and the experimental results tend to be quite limited.…”
Section: Introductionmentioning
confidence: 99%